18F-NaF PET/CT Images of Cardiac Metastasis From Osteosarcoma. (September 2016) - Chou, Yi-Hsien; Ko, Kuan-Yin; Cheng, Mei-Fang; Chen, Wei-Wu; Yen, Ruoh-Fang
Abstract : Abstract: Osteosarcomas are aggressive with a high incidence of recurrence and metastasis. Cardiac osteosarcoma metastasis is rare. We described a 17-year-old boy who had right distal femoral osteosarcoma with lung metastases. During follow-up, right ventricular (RV) metastasis was noted and confirmed by histopathological examination of the surgical specimen. 18 F-NaF PET/CT was then arranged 1 month after debulking surgery for residual tumor survey. The images showed intense 18 F-NaF uptake at RV region, suggestive of residual cardiac metastases.